CERVICAL CANCER: EARLY DETECTION AND EDUCATIONAL ACTIONS WITH UNIVERSITY STUDENTS - Vieira, Rodrigo Covre (2017)
Background: Cervical cancer (CC) is the most common cancer among women from northern Brazil. The periodic performance of Pap testing enables the identification of precursor lesions of cancer and provides high rates of recovery. Objectives: To promote educational measures and early detection of CC among university students, using the Pap test, the polymerase chain reaction (PCR) test for human papillomavirus (HPV), and advice about the risk factors associated with viral infections. Methods: This study is part of a university extension program focused on health care for adolescents and young public university students in the city of Belem do Pará, in northern Brazil. We conducted a descriptive study in the years 2013 and 2014 that involved 329 students. The students completed a socio-epidemiological questionnaire and provided cervico-vaginal material for cytological and PCR analysis. Results: The profile of the female participants of the study was as follows: aged 25 years or less (n = 202; 61.3%); non-smokers (n = 327; 99%); single (n = 298; 90%); multiple sexual partners (n = 199; 60.4%). Cytological abnormalities were observed in 12.8% (n = 42) of the samples and HPV infection was found in 25.8% (n = 85). Abnormal cytology results, where the presence of viral DNA was confirmed by PCR, were more frequent in younger women. Statistically significant associations were demonstrated between HPV infection and the occurrence of low grade and high grade squamous intraepithelial lesions (LSIL/HSIL), the age at menarche, and parity. Conclusion: The extension activity provided wide coverage of the target population. The high percentages of cytological abnormalities and HPV infections observed in the study reinforce the importance of university extension in helping to prevent sexually transmitted infections and CC in the study region.